A finite element analysis on the execution effects of two novel distalization sequences in clear aligners - Xing, Hongcheng; Li, Hui; Zhang, Dongliang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveCurrent clear aligners have the problem of long treatment duration, and the effect of traditional molar distalization sequences is not ideal. To address these issues, this study proposes a new molar distalization sequence. It uses finite element analysis to simulate the long-term movement of teeth, comparing the effectiveness of the new sequence with traditional ones in moving molars backward.MethodsA standard dental arch model with normal shape was selected, and the same target positions were set. Three different movement sequences were simulated: V-pattern (21stages), ZC (abbreviation of researchers Zhang and Chang; 22 stages), and CZC (an upgraded version of ZC; 17 stages). The final positions of teeth after long-term movement were calculated, and the 3D movements (including translation and rotation) of teeth from their initial positions to the final positions in each sequence were analyzed and compared with the preset target positions.ResultsThe comparison showed that the final tooth positions in the CZC sequence were closest to the target positions, followed by the ZC sequence, while the V-pattern had the largest deviation from the target.ConclusionThe CZC sequence proposed in this study can shorten orthodontic treatment time and improve treatment effectiveness, providing a new idea for the design of molar distalization sequences.